Psychological status of medical staff dedicated to nucleic acid collection in COVID-19 epidemic during closed-loop management: A cross-sectional study - Mingzhu Sun; Xiaowei Li; Jie Yao; Xi Huang; Yujuan Kang; Zixuan Li (Frontiers Media S.A., 2023)
BackgroundTo investigate the depression, anxiety and somnipathy situation occurred in the nucleic acid collection staff during the closed-loop management period of COVID-19. And try to understand the influencing factors of related psychological status.MethodsA cross-sectional study of 1,014 nucleic acid collection staff from seven Chinese hospitals was conducted. Various investigation methods were involved in the questionnaires to collect data, including 12-items self-made questionnaire survey of basic demographic information, 9-items patient health questionnaire depression scale (PHQ-9), 7-items generalized anxiety disorder scale (GAD-7) and Pittsburgh sleep quality index (PSQI). Data analysis was performed using SPSS version 26.0 and Excel software. Mann-Whitney U-test, Chi-square test, correlation analysis, mono-factor analysis and binary logistic regression were applied accordingly for further analysis.ResultsThe positive rate of depression, anxiety and sleep disorder of 1,014 nucleic acid collectors under closed-loop management were 33.5, 27.2, and 50.1%, respectively. Depression was significantly positively correlated with anxiety and sleep (P < 0.05). The scores of depression scale were positively correlated with the age and the fear for infection (r = 0.106, 0.218, both P < 0.05); The scores of anxiety scale were also positively correlated with the age and the fear for infection (r = 0.124, 0.225, both P < 0.05); The length of service, collection time and the degree of worry about infection and was positively correlated with the score of sleep scale (r = 0.077, 0.074, 0.195, both P < 0.05); Education level had a significant negative association with PHQ-9, GAD-7 and PSQI (r = −0.167,−0.172, both P < 0.05). Binary logistic regression analysis showed that age, technical title, education level, collection time, collection frequency, collection location, fear for infection and external environment were important influencing factors of depression, anxiety and sleep disorders.ConclusionThe results of this study suggested that when carrying out nucleic acid collection mission, managers should intervene to optimize the collection location, control the duration of each collection mission, replace the collection staff in time and pay close attention to the psychological state of the collection staff.